Review of thumb carpometacarpal arthritis classification, treatment and outcomes - Gillis, Joshua (Pulsus Group Inc, 2011)
Thumb carpometacarpal osteoarthritis (CMC OA) is a common disease, affecting up to 11% and 33% of men and women in their 50s and 60s, respectively, which leads to pain, laxity and weakness of the CMC joint. Based on the staging of the CMC OA, different forms of treatment can be used, including both conservative and surgical measures. Surgical options include osteotomy, trapezial excision, ligament reconstruction with or without tendon interposition, and various prosthetic interpositional implants with or without trapezial excision. The present article reviews the staging of CMC OA, the evaluation of hand function using patient-reported questionnaires, and outcomes of both conservative and surgical treatments. The present review also introduces a commercially available interpositional spacer surgical technique for CMC OA and the early evidence that the literature has shown for improving hand function, strength and stability of the thumb CMC joint postoperatively.